Soil Bacteriome Resilience and Reduced Nitrogen Toxicity in Tomato by Controlled Release Nitrogen Fertilizer Compared to Urea - Carley R. Rohrbaugh; Mary M. Dixon; Jorge A. Delgado; Daniel K. Manter; Jorge M. Vivanco (Applied Microbiology, 2023)
Controlled release fertilizers (CRFs) mitigate negative effects of high nitrogen (N) fertilization rates, such as N toxicity and soil N loss. However, it is unknown if potentially toxic rates of CRF and quick release fertilizer differentially affect soil bacterial communities. To examine potential N toxicity effects on soil microbial communities, we grew tomato (Solanum lycopersicum “Rutgers”) for eight weeks in soils that were fertilized with high levels of quick release or controlled release urea and in soils with either low or high initial microbial N competitor populations. In both soils, we observed N toxicity in urea-fertilized tomatoes, but toxicity was ameliorated with CRF application. Controlled release fertilization increased soil N retention, thereby reducing soil N loss. While N toxicity symptoms manifested in the plant, the soil microbiome was only minorly affected. There were subtle differences in soil bacterial populations, in which nitrifying bacteria accumulated in soils fertilized at high N rates, regardless of the type of N fertilizer used. Ultimately, CRF reduced plant N toxicity symptoms but did not change the soil microbiome compared to quick release urea. These results show that while there are clear benefits of CRF regarding N toxicity tolerance on crops, the soil microbiome is resilient to this abiotic stressor.